Isolation and Physicochemical Properties of Rice Bran Protein from Heat-Stabilized Rice Bran - Inneke Kusumawaty; Dedi Fardiaz; Nuri Andarwulan; Sri Widowati; Slamet Budijanto (UNEJ e-Proceeding, 2014)
Isolation and the physicochemical properties of rice bran protein concentrate (RBPC) produced from unstabilized and heat-stabilized Pandanwangi and Ciherang rice bran were studied. Rice bran stabilization process optimization done on previous research resulted in the extrusion conditions at a temperature of 130.96oC and screw speed 26.65 Hz. Kjeldahl analysis showed that protein content of unstabilized rice bran protein concentrates (URBPC) and stabilized rice bran protein concentrates (SRBPC) of Pandanwangi and Ciherang were 60.76%, 61.38%, 60.19%, and 60.23% respectively. Amino acid composition showed that polar amino acid composition of RBPC Ciherang was higher than that in Pandanwangi leading to its solubility. The protein percentage of acid-soluble glutelin of Pandanwangi was higher than that in Ciherang rice bran protein concentrate. The molecular weight were in range from 11.19 to 60.29 kDa. Glutelin differentiated into α-glutelin (30-39 kDa) and β-glutelin (19-25 kDa). The  RBPCs from two varieties had similar denaturation temperatures (77.22 - 77.99oC) with enthalpy ranged between 109.72 J/g and 200.98 J/g. Foaming stability and emulsion activities had similiar pattern with solubilities profile and showed no significant difference between varieties (p> 0.05). This finding shows potential protein concentrate of  both heat-stabilized and unstabilized rice bran as food ingredient. Keywords: Heat-stabilized rice bran, rice bran protein, physicochemical properties